Zr modified SrNbO2N as an active photocatalyst for water oxidation under visible light illumination. Issue 14 (17th June 2020) - Lin, Guoan; Wang, Ran; Cao, Tongcheng; Yuan, Liangxi; Xu, Xiaoxiang
Abstract : Zr modification induces porous microstructures, inhibits defect formation and ameliorates the surface hydrophilicity of SrNbO2 N, resulting in good photocatalytic activity. Abstract : With an absorption edge as far as 690 nm, SrNbO2 N holds great promise for solar energy conversion. However, very poor photocatalytic activity is generally seen for SrNbO2 N, limiting its practical applications as a photocatalyst. In this work, SrNbO2 N is modified by introducing Zr at B sites, i.e. SrNb1− x Zr x O2+ y N1− y (0 ≤ x ≤ 1), which are then investigated as photocatalysts for water oxidation reactions. Zr modification not only induces porous microstructures and inhibits the formation of Nb 4+ defects, but it also ameliorates the surface hydrophilicity of SrNbO2 N. Clear improvements in photocatalytic water oxidation have been realized after Zr modification and an apparent quantum efficiency of as high as 1.44% has been achieved. Further analysis of the band edge alignments suggests that Zr modification positively shifts the valence band edge of SrNbO2 N, which favors water oxidation reactions.